2010
DOI: 10.1063/1.3309769
|View full text |Cite
|
Sign up to set email alerts
|

The maximum possible magnetocaloric ΔT effect

Abstract: The current boom of research activity in magnetocaloric materials science is fuelled by the expectation that new advanced refrigerants may be found whose ΔT will significantly surpass that of gadolinium (Gd) metal (2.6–2.9 K/T). Because of this expectation, the main effort in the field has been diverted from the important issues of refrigerator design to the routine characterization of magnetic materials. Estimating the maximum adiabatic temperature change that can be achieved in principle by applying a certai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 19 publications
2
33
0
Order By: Relevance
“…A similar conclusion was reached by Zverev et al, in considering the maximum possible ∆T ad near a Curie transition [21]. The authors started from the approximation that, within a small temperature interval, ( ∂M ∂T ) H is constant, and showed that the optimum value of ∆T max ad is…”
Section: Fundamental Magnetothermal Propertiesmentioning
confidence: 59%
See 1 more Smart Citation
“…A similar conclusion was reached by Zverev et al, in considering the maximum possible ∆T ad near a Curie transition [21]. The authors started from the approximation that, within a small temperature interval, ( ∂M ∂T ) H is constant, and showed that the optimum value of ∆T max ad is…”
Section: Fundamental Magnetothermal Propertiesmentioning
confidence: 59%
“…Since ∆T ad is the temperature difference between two isofield S (T ) curves, the bound on entropy change yields a bound on ∆T ad . Two limiting scenarios, described in [21] arise from extremes in ∂T c /∂H as shown schematically in Figure 1. If ∂T c /∂H is small, ∆T ad is equal to the temperature width, ∆T w , of ∆S , which is ∂T c /∂H × H max and is therefore linear in ∂T c /∂H.…”
Section: Fundamental Magnetothermal Propertiesmentioning
confidence: 99%
“…To study this reduction in RC FWHM , the compositional dependence of full temperature width at half maximum ͑␦T FWHM ͒ of ͉⌬S M pk ͉ was plotted ͓inset of The decrease in RC for the La alloy series could be attributed to the reduction in ͉⌬S M pk ͉ ͑RC being proportional to ͉⌬S M pk ͉ and ␦T FWHM ͒ since ͉⌬S M pk ͉ generally plays a dominant role in RC maximization for SOMT materials. 27 For the Ce alloy series, the reduced ͉⌬S M pk ͉ and ␦T FWHM contributes to a much lower RC value, e.g., in the Ce15 alloy. For the Gd series, the large decreasing trend of RC could be attributed to the large reduction in ͉⌬S M pk ͉ with Gd addition.…”
Section: Influence Of La and Ce Additions On The Magnetocaloric Effecmentioning
confidence: 99%
“…6,13 In the simplest approximation, the adiabatic temperature change may be simplified to ∆T ad (T,Y applied ) = (∂T t /∂Y i )Y applied for values of (∂T t /∂Y i ) that are below the value at which ∆T ad (T,Y applied ) is maximised. Beyond the value of (∂T t /∂Y i ) that maximises ∆T ad , ∆T ad (T,Y applied ) is instead related to the isothermal entropy change via the heat capacity, C p through ∆T ad = −T∆S/C p .…”
Section: Evaluating Caloric Potentialmentioning
confidence: 99%